Уточнение описания самцов Subeucalanus subtenuis и Subeucalanus mucronatus из Аравийского моря - Прусова, И.Ю. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2003)
Самцы Subeucalanus subtenuis (Giesbrecht, 1888) и S. mucronatus (Gies-brecht,1888) были окрашены по методу Флеминджера (Fleminger, 1973) и идентифицированы по характеру расположения наружных пор на цефалотораксе и абдомене. Исследованы морфологические особенности каждого из видов. Выявлены различия между видами в вооружении щетинками щупика мандибулы. Проанализованы имеющиеся в литературе описания данных видов. Males of Subeucalanus subtenuis (Giesbrecht, 1888) and S. mucronatus (Gies-brecht, 1888) were stained according to the Fleminger's (1973) method and identified based on the patterns of integumental pores of the cephalothorax and abdomen. Morphological features of each species are examined. The difference between two species in mandibular palp setation is revealed. Other available descriptions of these species were analyzed.